2000
DOI: 10.1002/1522-7278(2000)15:3<160::aid-tox2>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity toDaphnia magna of effluents containing Cd, Zn, and a mixture Cd-Zn, after metal removal byChlorella vulgaris

Abstract: Daphnia magna was used as a test organism for assessing the toxicity remaining in simulated effluents containing cadmium, zinc, and a cadmium-zinc mixture, after these metals were removed with suspended and immobilized Chlorella vulgaris cultures. The percentage of removal was ( ) higher 84.7% for cadmium in the metal mixture with immobilized cultures. The LC value was lower 50 ( ) for the residual cadmium single and in the mixture in the effluent after treatment with suspended cultures. The acute toxicity res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A similar antagonistic effect of Cu and Zn was observed in L. vannamei and Daphnia magna by Frías-Espericueta et al (2003) and by Cañizares-Villanueva et al (2000), although Negilski et al (1981) and Vanegas et al (1997) found a synergistic effect in the crustaceans Callianassa australiensis and Litopenaeus setiferus exposed to a mixture Cd-Zn, which could be explained by genetic differences or by different chemical characteristics of the respective aquatic environments.…”
Section: Discussionmentioning
confidence: 62%
“…A similar antagonistic effect of Cu and Zn was observed in L. vannamei and Daphnia magna by Frías-Espericueta et al (2003) and by Cañizares-Villanueva et al (2000), although Negilski et al (1981) and Vanegas et al (1997) found a synergistic effect in the crustaceans Callianassa australiensis and Litopenaeus setiferus exposed to a mixture Cd-Zn, which could be explained by genetic differences or by different chemical characteristics of the respective aquatic environments.…”
Section: Discussionmentioning
confidence: 62%
“…However, the absence of this species in natural environments makes it an inappropriate bioindicator of natural and anthropogenic processes (Kammenga and Risken, 1996). Comparing with other invertebrate taxa, A. avenae and C. persegnis also seem to be more tolerant to the toxicity of either Cu or Zn than the water flea Daphnia magna (48 h LC50 of 4.13-11.48 mg Zn/L) (Cañizares-Villanueva et al, 2000), the pink hydra Hydra vulgaris (96 h LC50 of 2.3-7.4 mg Zn/L and 0.032 mg Cu/L) (Karntanut and Pascoe, 2000;Holdway et al 2001), the earthworm Enchytraeus bucholzi (48 h LC50 of 0.43 mg Cu/L) (Willuhn et al, 1996), and the sandy gastropod Nassarius festivus (96 h LC50 of 0.36 mg Cu/L and 1.76 mg Zn/L) (Cheung et al, 2002). This higher resistance of soil nematodes to heavy metals can explain the high capability of recovery after perturbation of nematode community (Bengtsson, 2002).…”
Section: Discussionmentioning
confidence: 89%
“…These results are consistent with previous reports of a protective effect of Zn against Cd toxicity. Less-than-additive toxicity of Cd-Zn mixtures to D. magna was reported by Attar and Maly [25] (based on a concentration-addition-type model in 3 separate toxicity tests with Cd-Zn mixtures) and by Cañizares-Villanueva et al [26] (based on S toxic unit values for 50% mortality in 2 separate toxicity tests with Cd-Zn mixtures). However, Shaw et al [27] did not observe statistically significant deviations from additivity in D. magna exposed to Cd-Zn mixtures (using an additive-effects model); and Wicklund Glynn et al [28] reported additive chronic toxicity in juvenile minnows (Phoxinus phoxinus) exposed to a Cd-Zn mixture.…”
Section: Cd-zn Binary Mixturesmentioning
confidence: 89%